Teachers’ Perception of Online Professional Development: A Case of Chinese High School Teachers in Ningxia - Kong, Ling-di; Saidon, Mohd Kasri; Saidin, Khaliza (Academic Research Publishing Group, 2017)
The importance of utilizing the Internet to alleviate a range of training problems has been proved and accepted by teachers and educators. However, Chinese researchers found that less than 50% teachers eager to participate in online courses for their professional development. Therefore, research objective of this study was to identify Chinese high school teachers’ perception toward usefulness and ease of use of online professional development (OPD). The participants consist of 120 teachers from 3 high schools in Ningxia.The instrument for data collection was 12-item questionnaire.The researchers adopted the Cronbach Alpha method to determine the reliability of the instrument. A reliability index of 0.84 was obtained.Two research questions were structured and data collected were analyzed using mean and standard deviation.Findings revealed that there was significant positive effect on the usefulness and ease of use of OPD among Chinese high school teachers.It was also recommended that to stimulate Chinese high school teachers’ positive attitude toward OPD, the quality of OPD courses should be emphasized more by online educators.